Focused ion beam sample preparation method for reducing curtain effect of porous transmission sample
By employing a multi-functional sample stage tilting and directional platinum protective layer deposition technology, the curtain effect problem in porous oxide film samples in traditional sample preparation methods has been solved, improving sample quality and sample preparation success rate, and achieving effective protection of the pore structure.
Patent Information
- Application Number
- CN202511159168.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-25
AI Technical Summary
Traditional focused ion beam (FIB) sample preparation techniques do not adequately protect porous oxide film samples, resulting in severe curtain effect, poor sample quality, and low sample preparation success rate, especially for oxide film samples with high porosity.
By employing a multi-functional sample stage tilt angle and directional platinum protective layer deposition technology, and through a rotation-tilt-selective coating method, effective protection of porous structures and a significant reduction of the curtain effect are achieved.
It significantly reduces the curtain effect, improves the success rate and quality of porous transmission sample preparation, ensures the integrity of the pore structure, and provides a reliable sample basis for subsequent microstructure analysis.
Smart Images

Figure CN121007748A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of material analysis, and particularly to a focused ion beam sample preparation method for reducing the curtain effect of a porous transmission sample. BACKGROUND
[0002] Focused ion beam technology is an important method for preparing transmission electron microscope samples and plays a key role in material science research. However, for porous oxide film samples formed by high-temperature water vapor oxidation, traditional focused ion beam sample preparation technology faces serious technical challenges.
[0003] The high-temperature water vapor oxidation porous oxide film sample has the following characteristics: first, the multi-layer structure is complex, and the FeAl2O4 outer layer and the alpha-Al2O3 inner layer formed by high-temperature water vapor oxidation of FeCrAl alloy under certain conditions have different physical and chemical properties, and the Cr-coated zirconium alloy has Kirkendall holes induced by element diffusion during high-temperature processes, and there will also be complex interface effects between the coating and the substrate; second, the pore structure is developed, and the porosity of the oxidation film of the material serving at extremely high temperatures usually reaches 20% to 40%, and the pore size distribution is uneven; in addition, the mechanical properties differ greatly, and the hardness and toughness of the oxidation film and the substrate differ significantly. In the traditional focused ion beam sample preparation process, such samples are prone to serious curtain effect. The curtain effect refers to the formation of a striped undulation on the sample surface during ion beam sputtering due to the difference in sputtering rate of different phases and the existence of pore structure, which seriously affects the sample quality and the subsequent transmission electron microscope observation effect.
[0004] The existing technology mainly uses the following methods to solve the curtain effect problem:
[0005] First, the pre-deposited protective layer technology: a platinum or tungsten protective layer is pre-deposited on the sample surface to reduce direct ion beam damage, but for porous structures, the traditional vertical deposition method cannot effectively fill the inside of the pores, and the protection effect is limited. Second, low-current polishing technology: using a low-current ion beam for final polishing can improve the surface quality to a certain extent, but for the curtain effect structure that has already been formed, the polishing effect is limited, and it is easy to cause excessive thinning of the thin area. Third, multi-step thinning technology: thinning is performed by adjusting the ion beam parameters in stages, but the process is complex, and the protection of the porous structure is still insufficient.
[0006] For FeCrAl alloys and Cr-coated zirconium alloys used in the nuclear industry, the study of their high-temperature steam oxidation behavior is of great significance for evaluating material performance under extreme service environments. FeCrAl alloys, as candidate materials for accident-tolerant fuel cladding, exhibit oxidation behavior in high-temperature steam environments that directly affects the safety of nuclear reactors. For zirconium alloys, as traditional nuclear fuel cladding materials, the microstructural evolution of the oxide film in the coating material influences the mechanical properties and corrosion resistance of the cladding. High-temperature oxidation samples of these materials typically possess complex porous oxide film structures, making it difficult to obtain high-quality transmission electron microscopy samples using traditional sample preparation methods.
[0007] Therefore, existing technologies have the following problems: insufficient protection of porous structures, with the curtain effect severely affecting sample quality; low sample preparation success rate, especially for oxide film samples with high porosity; lack of specialized sample preparation techniques for specific porous structures; and existing protective layer deposition methods cannot effectively fill complex three-dimensional porous structures.
[0008] In view of this, the present invention is proposed. Summary of the Invention
[0009] The purpose of this invention is to provide a focused ion beam (FIP) sample preparation method to mitigate the curtain effect in porous transmission samples, thereby addressing the problems existing in the prior art. Current FIP sample preparation techniques do not provide sufficient protection when processing high-temperature oxidized porous samples, resulting in a severe curtain effect, poor sample quality, and low preparation success rate. To solve these technical problems, this invention provides a FIP method to mitigate the curtain effect in porous transmission samples. Through a multi-functional sample stage tilt angle and directional platinum protective layer deposition technology, effective protection of the porous structure and a significant reduction in the curtain effect are achieved.
[0010] To achieve the above objectives, the present invention provides the following solution:
[0011] This invention provides a focused ion beam sample preparation method to mitigate the curtain effect in porous transmission samples, comprising the following steps:
[0012] (1) Sample pretreatment: The FIB sheet extracted from the surface of the porous sample oxidized by water vapor is welded onto the copper mesh at the 38-degree pre-tilt stage of the multi-functional sample stage of the focused ion beam equipment.
[0013] (2) Preliminary thinning: The FIB sheet is thinned using a focused ion beam at a 0-degree tilt angle;
[0014] (3) Porous structure identification: During the thinning process, the morphological characteristics of the FIB sheet are monitored through the electron beam window. When a sudden change in the number or size of the holes is found, the processing is stopped, and the thickness of the FIB sheet is ensured to be no less than 300 nm to avoid sample bending that may occur in subsequent deposition steps.
[0015] (4) Rotation-tilt-selective deposition: Rotate the multifunctional sample stage 180 degrees and make the ion beam window perpendicular to the surface of the FIB sheet to perform gas-assisted platinum deposition to fill the holes of the FIB sheet.
[0016] (5) Restore the angle thinning: tilt the multifunctional sample to 0 degrees, then rotate it 180 degrees to restore the thinning angle in step (2), and continue to use a focused ion beam to thin it to the target thickness;
[0017] (6) Sample purging: Surface purging is performed using an ion beam.
[0018] Furthermore, the high-temperature steam-oxidized porous sample is a porous oxide film sample formed by the oxidation of FeCrAl alloy or Cr-coated zirconium alloy in a high-temperature steam environment. This type of sample has a typical multilayer porous structure and is the sample type where the curtain effect is most likely to occur and most difficult to eliminate.
[0019] Furthermore, the focused ion beam equipment is a Helios 5CX dual-beam focused ion beam system. This equipment features high-precision sample stage tilting and excellent ion beam performance.
[0020] Furthermore, the gas-assisted platinum deposition power is 30 kV, the deposition current is 80 pA, and the deposition thickness is 30–50 nm. The platinum deposition time is adjusted according to the pore density and depth.
[0021] Furthermore, in step (4), when using focused ion beam thinning, the current of the focused ion beam is gradually reduced; for high-hardness samples (such as the Cr-coated Zr-4 alloy oxide film containing ZrO2 in Example 1), coarse thinning can be performed first at 30kV and 2.3nA to improve efficiency, then secondary thinning can be performed at 30kV and 0.79nA, and finally fine thinning can be performed at 30kV and 80pA.
[0022] For samples with conventional hardness (such as the 10Cr-FeCrAl alloy oxide film in Example 2), 30kV and 0.79nA are used in the rough thinning stage, and 30kV and 80pA are used in the fine thinning stage to finally obtain the sample with the target thickness.
[0023] The apparatus used in this invention includes: a Helios 5CX dual-beam focused ion beam system, a multi-functional sample stage, a 38-degree pretilt stage, a copper mesh, a gas-assisted deposition system, and a real-time monitoring system.
[0024] The present invention also provides porous transmission samples prepared by the above-mentioned focused ion beam sample preparation method for reducing the curtain effect of porous transmission samples.
[0025] Based on the above problems, this invention proposes a focused ion beam sample preparation method to reduce the curtain effect in porous transmission samples. By using a rotation-tilt-coating method, the curtain effect in the porous transmission sample preparation process is greatly reduced, significantly improving the success rate and quality of porous transmission sample preparation.
[0026] The present invention discloses the following technical effects:
[0027] This invention employs tilt-oriented deposition technology, solving key technical challenges in traditional preparation processes. This invention allows the deposited Pt to vertically enter the pores for effective filling, significantly reducing the curtain effect during subsequent ion beam processing and fundamentally improving the filling quality. Simultaneously, this technology substantially increases the success rate of porous oxide film preparation from 35% of traditional methods to over 80%, effectively enhancing work efficiency and production stability. Furthermore, this invention maintains the integrity of the pore structure through directional protection technology, achieving a pore structure integrity rate of over 95%, providing a reliable sample basis for subsequent microstructure analysis and performance characterization, and ensuring the accuracy and reproducibility of analytical results.
[0028] This invention offers significant advantages in terms of process flexibility and practicality. The process allows for flexible adjustment of the tilt angle and deposition parameters based on the pore characteristics and size requirements of different samples, exhibiting strong adaptability and a wide range of applications. Developed based on standard Helios equipment, this invention fully utilizes existing equipment resources, demonstrating excellent equipment compatibility and requiring no additional equipment investment, thus reducing the cost and barriers to technology promotion. By integrating a real-time monitoring system and step-by-step processing technology, it enables precise control of processing timing and effects, achieving accurate quality control, ensuring process stability and product quality consistency, and laying a solid foundation for industrial applications. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is a schematic diagram of the overall process of the method of the present invention;
[0031] Figure 2 This diagram shows the macroscopic morphology of the sample stage inside the Helios chamber and its position at various angles. Specifically: initial thinning state (a, b); state after rotating 180 degrees from the initial thinning state (c, d); and state after a 14-degree tilt following a 180-degree rotation from the initial thinning state (e, f).
[0032] Figure 3 This is a schematic diagram of the curtain effect in the conventional thinning method for preparing porous samples without plating in Example 2.
[0033] Figure 4 This is a SEM image of the FIB sampling location of the Cr-coated Zr-4 alloy pipe sample oxidized by high-temperature water vapor in Example 1.
[0034] Figure 5 This is a schematic diagram of the hole repair plating of the Cr-coated Zr-4 alloy pipe sample subjected to high-temperature water vapor oxidation in Example 1.
[0035] Figure 6 This is a comparison of the FIB morphology of the Cr-coated Zr-4 alloy pipe before and after high-temperature steam oxidation replating in Example 1.
[0036] Figure 7 This is a comparison of the FIB morphology of the 10Cr-FeCrAl alloy before and after high-temperature steam oxidation plating in Example 2.
[0037] Figure 8 The images show top views of the FIB samples obtained after the conventional thinning method (a) without plating and the rotation-tilt-plating Pt method (b) in Example 2.
[0038] Figure 9 This is a high-resolution image of the transmission sample-alumina phase of Example 2 prepared by the method of the present invention.
[0039] Figure 10 This is a morphology image of the AZ91 magnesium alloy FIB sample in Comparative Example 1 of the present invention after replating.
[0040] Figure 11 This is a morphology image of the high-entropy alloy sample in Comparative Example 2 of the present invention after being re-plated by lead-bismuth corrosion FIB. Detailed Implementation
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0043] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0044] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0045] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0046] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0047] Figure 1 This is a schematic diagram of the overall process of the method of the present invention.
[0048] Figure 2 The diagram shows the macroscopic morphology of the sample stage inside the Helios chamber and the position of the sample stage at various angles, including: the initial thinning state (a, b), the state after rotating 180 degrees from the initial thinning state (c, d), and the state after 14 degrees of tilting after rotating 180 degrees from the initial thinning state and then plating Pt (e, f).
[0049] Example 1
[0050] This embodiment relates to the preparation of a transmission electron microscope sample of a porous oxide film formed by oxidizing a Cr-coated Zr-4 alloy pipe in a water vapor environment at 1340℃ for 600s.
[0051] (1) Sample pretreatment
[0052] The oxidized Cr-coated Zr-4 alloy tube sample was fixed to the multi-functional sample stage of the Helios 5CX focused ion beam equipment using conductive adhesive. The FIB sample was extracted from the sample surface and welded to the copper mesh of the 38-degree pre-tilt stage to complete the fixation and positioning before processing.
[0053] (2) Initial thinning
[0054] The focused ion beam is activated at a 0-degree tilt angle to perform thinning processing.
[0055] (3) Porous structure identification: During the thinning process, the morphological characteristics of the FIB sheet are monitored through the electron beam window. When the thinning reaches the intermediate stage, a porous structure with a porosity of about 30% is observed in the oxide film through the electron beam window. The pore size is mainly distributed in the range of 30 to 80 nm. At this time, the processing is stopped and the thickness of the FIB sheet is 320 nm to avoid sample bending that may be caused by subsequent deposition steps.
[0056] (4) Rotation-tilt-selective plating
[0057] Rotate the multi-functional sample stage 180 degrees, then tilt it 14 degrees to make the ion beam window nearly perpendicular to the sample surface. Start the gas-assisted platinum deposition system, setting the deposition parameters to 30kV voltage, 80pA current, 40 seconds deposition time, and a deposition thickness z of 100nm, filling the pores to the original surface height. At this vertical angle, the platinum precursor gas can effectively penetrate and fill the pores, forming a protective filling layer.
[0058] (5) Restore angle thinning
[0059] To address the high hardness of ZrO2, the ion beam parameters were adjusted for stepwise thinning: a current of 2.3 nA was used in the coarse thinning stage to improve efficiency, 0.79 nA was used in the second thinning stage, and the current was switched to 80 pA in the fine thinning stage to ensure surface quality. Finally, the sample was thinned to the target thickness of approximately 90 nm.
[0060] (6) Sample purging: Surface purging is performed using an ion beam.
[0061] A 5kV low-energy ion beam was used for surface purging, with a current of 41pA and a purging time of 3 minutes, to remove the amorphous damage layer on the surface and improve the surface quality of the sample.
[0062] Experimental results show that for Cr-coated Zr-4 alloy pipes that have undergone high-temperature steam oxidation, when preparing porous oxide film FIB samples using the above method, the curtain effect intensity of the samples is significantly reduced, the surface roughness Ra is reduced from 17.4 nm to 3.3 nm, a reduction of 84.5%, and the number and undulation of vertical stripes are significantly reduced; the oxide film-substrate interface remains intact without artificial defects; the porous structure is effectively protected, and the pore morphology is clearly distinguishable.
[0063] Example 2
[0064] This embodiment relates to the preparation of a porous oxide film transmission electron microscope sample of a 10Cr-FeCrAl alloy after prior corrosion and subsequent oxidation in a high-temperature water vapor environment at 1200℃ for 2 hours.
[0065] (1) Sample pretreatment
[0066] The oxidized 10Cr-FeCrAl sample was fixed to the multi-functional sample stage of the Helios 5CX focused ion beam equipment using conductive adhesive. The FIB sample was extracted from the sample surface and welded to the copper mesh of the 38-degree pre-tilt stage to complete the fixation and positioning before processing.
[0067] (2) Initial thinning
[0068] At a 0-degree tilt angle, a 30kV Ga... + Ion beam is used for rough thinning, with the ion beam current set to 0.79 nA, and initial grooves are machined on both sides of the target area.
[0069] (3) Porous structure identification:
[0070] During the thinning process, the morphological changes of the sample were monitored in real time through an electron beam window. When the thinning reached a certain stage, an abrupt change in the porous structure of the sample surface was observed: the porosity was about 25%, the pore size was distributed in the range of 50-100 nm, and the thickness of the FIB sheet was 330 nm. At this point, the thinning was immediately stopped.
[0071] (4) Rotation-tilt-selective plating
[0072] Rotate the multi-functional sample stage 180 degrees, then tilt it 14 degrees to make the ion beam window perpendicular to the sample surface. Start the gas-assisted platinum deposition system, setting the parameters to 30kV voltage, 80pA current, and a deposition time of 45 seconds to form a 50nm thick platinum protective layer. At this vertical angle, the platinum precursor gas can effectively fill the pores in the central region of the sample.
[0073] (5) Restore angle thinning
[0074] The sample stage was tilted from 14 degrees to 0 degrees, and then rotated 180 degrees to restore the normal thinning angle. Since the pores were effectively filled with platinum, normal ion beam thinning could continue at this point, and the curtain effect was significantly reduced. Ion beam parameters were adjusted in stages for thinning: a current of 0.79 nA was used in the coarse thinning stage, and the current was switched to 80 pA in the fine thinning stage, ultimately reducing the sample to the target thickness of approximately 80 nm.
[0075] (6) Sample purging
[0076] A 5kV low-energy ion beam was used for surface purging, with a current of 41pA and a purging time of 3 minutes, to remove the amorphous damage layer on the surface and improve the surface quality of the sample.
[0077] Experimental results show that the quality of the FeCrAl alloy oxide film samples prepared using the method of this embodiment is significantly improved: compared with the FIB samples that are directly thinned without re-plating (Figure 3 As shown, the FIB sample prepared by the method of the present invention exhibits a significantly reduced curtain effect, with the surface roughness Ra decreasing from 25.6 nm to 4.3 nm, a reduction of 83.2%. The number and undulation of vertical stripes are also significantly reduced. The pore structure remains intact without collapse. The FeAl2O4 / α-Al2O3 interface is clear and layered. The sample thickness uniformity is ±6 nm, which is significantly better than ±22 nm of the traditional method.
[0078] Figure 3 This is a schematic diagram of the curtain effect in Example 2, which shows the porous sample prepared using the conventional thinning method without plating.
[0079] Among them, the FIB samples that are directly thinned without plating are thinned by directly tilting them at ±1.5 degrees after soldering them to a copper mesh. When encountering samples with many holes on one side during thinning, the uneven material hardness along the ion beam's path causes a curtain effect as the ion beam advances. The more numerous and larger the holes, the more pronounced the curtain effect. It is evident that when there are many or large holes in the middle of the sample, the curtain effect (vertical undulations) is particularly significant in FIB samples thinned using conventional methods, which greatly affects the image quality under a transmission electron microscope.
[0080] Figure 4 This is a SEM image of the FIB sampling location of the Cr-coated Zr-4 alloy pipe sample subjected to high-temperature steam oxidation in Example 1. The image preliminarily reveals that the central portion of the sample to be prepared contains numerous pores.
[0081] Figure 5 This is a schematic diagram of the porosity repair plating of the Cr-coated Zr-4 alloy pipe sample subjected to high-temperature steam oxidation in Example 1. This is the core step of the 14-degree Pt layer repair plating method described in this invention. In actual operation, the entire FIB sheet can also be repaired, with the ultimate goal of filling the porosity in the middle area of the sample as much as possible. This example only targets the areas where the porosity is relatively significant for repair plating.
[0082] Figure 6 This is a comparison of the FIB morphology of the Cr-coated Zr-4 alloy pipe before and after high-temperature steam oxidation replating in Example 1. It can be seen that although a large number of holes appeared in the middle part of the sample, the curtain effect (black vertical lines) is not significant in the final image, and the overall thickness of the sample is very uniform, with no bending or perforation phenomena.
[0083] Figure 7 This is a comparison of the FIB morphology of the 10Cr-FeCrAl alloy before and after high-temperature steam oxidation plating in Example 2. Figure 6Similarly, there are many holes in the middle of the sample, but after the Pt plating method of the present invention, the overall uniformity of the final sample is good and the sample preparation effect is excellent.
[0084] Figure 8 The images show top views of the FIB samples obtained in Example 2 after the conventional thinning method (a) without plating and the rotation-tilt-plating Pt method (b). It can be seen that after plating, the sample uniformity is significantly improved. This is reflected in the top view by a significant reduction in the white edge areas on both sides of the sample (almost no white edges on the top and bottom sides of the sample in the right-hand image), indicating that the overall thickness of the sample is relatively uniform and that no bending or perforation phenomena occur.
[0085] Figure 9 The image shows a high-resolution image of a transmission sample-alumina phase prepared by the method of the present invention. The high-resolution image shows a clear dot matrix in a conventional transmission electron microscope, indicating that the method of the present invention is effective in reducing the curtain effect and improving sample quality when preparing porous oxide film FIB samples.
[0086] Comparative Example 1
[0087] This comparative example is a transmission electron microscope (TEM) sample of an oxide film formed on an AZ91 magnesium alloy after being oxidized at 500°C in air for 2000 hours. The TEM sample preparation parameters are the same as those in Example 2.
[0088] This alloy belongs to the Mg-Al-Zn magnesium alloy system, and its mass percentage composition is as follows: magnesium (Mg) balance (major component), aluminum (Al): 8.5-9.5%, zinc (Zn): 0.45-0.9%, manganese (Mn): 0.17-0.4%, silicon (Si): ≤0.08%, iron (Fe): ≤0.004%, nickel (Ni): ≤0.001%, copper (Cu): ≤0.025%, and other elements: ≤0.01% (such as beryllium, Be, etc.). The oxidation conditions are 2000 hours in an air atmosphere at 500 degrees Celsius in a box furnace.
[0089] Comparative Example 2
[0090] This comparative example is a transmission electron microscope (TEM) sample of a loose, porous oxide film formed after lead-bismuth corrosion of a high-entropy alloy. The parameters are consistent with those in Example 2. The material used for this FIB sample is a high-entropy alloy, with the following atomic percentages: Fe 35.1%, Ni 35.0%, Cr 13.1%, and Al 16.8%. The etching solution was a nuclear-grade LBE solution (44.5Pb-55.5Bi, wt.%), and the etching conditions were immersion at 500°C for 1000 hours.
[0091] Comparative Example 3
[0092] This comparative example is a transmission electron microscope (TEM) sample of a loose, porous oxide film formed on a 718 nickel-based alloy after lead-bismuth etching. The parameters are consistent with those in Example 2. The material used for this FIB sample is a 718 nickel-based alloy, with the following mass percentages: Fe 17.0%, Ni 53.2%, Cr 19.8%, Mo 3.0%, Ti 1.1%, and the remainder being trace elements such as Si, Mn, C, Al, Nb, and Ta. The etching solution is a nuclear-grade LBE solution (44.5Pb-55.5Bi, wt.%), and the etching conditions are immersion at 500°C for 1000 hours. For interface samples with significantly different radiation resistance, indiscriminate plating will result in the etching of the side with weaker radiation resistance.
[0093] Figure 10 The top view of the FIB sample cut from Comparative Example 1 - AZ91 magnesium alloy after 2000 hours of high-temperature oxidation at 500°C in air and then re-plating is shown. It can be seen that the equipment parameters of the method of this invention are prone to causing the sample to bend when the material is soft. Different materials need to be set with special re-plating parameters according to their material characteristics.
[0094] Figure 11 The image shows the morphology of the high-entropy alloy sample after lead-bismuth corrosion FIB re-plating in Comparative Example 2. It can be seen that for interface samples with significantly different radiation resistance, indiscriminate re-plating will lead to the etching of the side with weaker radiation resistance. In this sample, the lead-bismuth intrusion side was significantly damaged. The reason is that the lead-bismuth part is not resistant to ion beam irradiation and was significantly etched during the re-plating process, resulting in a large number of holes.
[0095] To verify the universality of the method of the present invention, the present invention compared the effects of different tilt angles on the coating effect. The high-temperature water vapor oxidation sample of 10Cr-FeCrAl alloy in Example 2 after pre-oxidation was selected, and directional coating experiments were carried out at three tilt angles of 10 degrees, 14 degrees and 18 degrees respectively.
[0096] The results show that at angles of 10 degrees and 18 degrees, because the ion beam is not perpendicular to the sample surface, some Pt accumulates on the outer surface of the pores during the Pt layer re-plating step. This leads to a decrease in the surface smoothness of the sample after re-plating, and the platinum filling depth and actual filling efficiency are significantly reduced, resulting in limited protection of the sample's pore structure. However, at an angle of 14 degrees (directly facing) or 14 ± 0.5 degrees (approximately perpendicular), the pore filling efficiency is the highest, and the sample surface is relatively smooth from a top view after re-plating. The curtain effect caused by uneven hardness within the sample is greatly weakened during subsequent thinning.
[0097] Through experimental parameter optimization, the optimal process parameters of this invention were determined to be: tilting plating angle of 14 degrees ± 0.5 degrees, deposition voltage of 30kV, deposition current of 80pA, and deposition thickness of 30-50nm. Under these parameters, the success rate of porous sample preparation can be stabilized at over 80%, and the sample quality is significantly improved.
[0098] The method of this invention has important application value in the nuclear industry, aerospace industry and other fields. In the nuclear industry, it can be used to study the high-temperature steam oxidation behavior of accident-tolerant fuel cladding materials FeCrAl alloy and coated zirconium alloy, providing microscopic mechanism support for nuclear reactor material optimization. In the aerospace industry, it can be used to characterize the microstructure of high-temperature alloy anti-oxidation coatings, providing technical basis for engine blade coating design.
[0099] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A focused ion beam sample preparation method for mitigating the curtain effect in porous transmission samples, characterized in that, Includes the following steps: (1) Sample pretreatment: The FIB sheet extracted from the surface of the porous sample oxidized by water vapor is welded onto the copper mesh at the pre-tilt position of the multi-functional sample stage on the focused ion beam equipment. (2) Preliminary thinning: The FIB sheet is thinned using a focused ion beam at a 0-degree tilt angle; (3) Porous structure identification: During the thinning process, the morphological characteristics of the FIB sheet are monitored. When a sudden change in the number or size of the holes is found, the processing is stopped, and the thickness of the FIB sheet is ensured to be no less than 300 nm. (4) Rotation-tilt-selective deposition: Rotate the multifunctional sample stage 180 degrees and tilt the multifunctional sample stage so that the ion beam window is perpendicular to the surface of the FIB sheet, and perform gas-assisted platinum deposition to fill the holes of the FIB sheet. (5) Restore the angle thinning: tilt the multifunctional sample to 0 degrees, then rotate it 180 degrees to restore the thinning angle in step (2), and continue to use a focused ion beam to thin it to the target thickness; (6) Sample purging: Surface purging is performed using an ion beam.
2. The focused ion beam sample preparation method for mitigating the curtain effect in porous transmission samples according to claim 1, characterized in that, The porous sample oxidized by water vapor is a porous oxide film sample formed by the oxidation of FeCrAl alloy or Cr-coated zirconium alloy in a water vapor environment.
3. The focused ion beam sample preparation method for mitigating the curtain effect in porous transmission samples according to claim 1, characterized in that, The focused ion beam device is a Helios 5CX dual-beam focused ion beam device.
4. The focused ion beam sample preparation method for mitigating the curtain effect in porous transmission samples according to claim 1, characterized in that, The gas-assisted platinum deposition power is 30kV, the deposition current is 80pA, and the deposition thickness is 30-50nm.
5. A porous transmission sample prepared by the focused ion beam sample preparation method for mitigating the curtain effect in porous transmission samples as described in any one of claims 1-4.
Citation Information
Patent Citations
Method for preparing transmission electron microscope sample
CN106289909A
Preparation method of transmission electron microscope sample with internal defects
CN118731067A
Method for producing gasket on converter slug operated with moving magnetic media
CN1487505A
Refilling method by ion beam, instrument for fabrication and observation by ion beam, and manufacturing method of electron device
US20030198755A1
Method and System of Creating a Symmetrical FIB Deposition
US20150369710A1